Nghiên cứu đối chiếu về ẩn dụ ý niệm TÌNH YÊU trong tiếng Anh và tiếng Việt = English and Vietnamese metaphorical conceptualization of love: A contrastive study /Nguyễn Văn Trào - Nguyễn, Văn Trào
This paper undertakes an in-depth investigation of the idioms that express the emotion (EIs) of LOVE in English and Vietnamese and aims to offer excellent opportunities for cross-language and cross-cultural comparison and analysis into metaphorical conceptualization of LOVE between the two languages. The analysis of the data was carried out for the English and Vietnamese individually following the Conceptual Metaphor Theory. This paper also aims to prove that the metaphorical conceptualization of LOVE in English and Vietnamese is influenced by not only physiological, but also cultural factors.